Biología básica de Cephanonomia stephanoderis parasitoide de la broca del cafe - Barrera, J.F.=700 1 Infante, F.; Castillo, A.; Gómez, J.; de la Rosa, W.
Sumario (Es)
Ilus.; 3 ref.
Keywords: COFFEA; HYPOTHENEMUS HAMPEI; PARASITOIDES; CONTROL BIOLOGICO; BIOLOGIA